Helicobacter pylori in the dental plaque of healthy Saudis - Contractor Qais; Tahir Mohammed; Naseem Shahzad; Ahmad Shamweel (The Saudi Journal of Gastroenterology, 1998)
The objective of this study is to determine the presence of Helicobacter pylori in the dental plaque of healthy Saudis and its relation to dental care. One hundred randomly selected healthy Saudis attending the dental clinic were assessed for oral hygiene and periodontal disease by dental examination. Information about the use of toothpaste, chewing stick, smoking and dentures was obtained. Samples of dental plaque were collected after scoring it according to the plaque index. Presence of H. pylori in the plaque was sought by a commercially available rapid urease test with a sensitivity of 94% and a specificity of 100%. The presence of H. pylori was indicated by a positive rapid urease test in 81 %. There was significant correlation of heavy dental plaque (plaque index score 3) with presence of H. pylori (p=0.03). We conclude that H. pylori is present in the dental plaque of most Saudis and this is due to poor oral hygiene.